Exemplars, models and principles in classical genetics (Scientiae Studia, 2005)
Taking as starting point the book of Sinnott and Dunn, Principles of genetics: an elementary text, with problems, that may be considered the first textbook of classical genetics in the Kuhnian sense, and the analyses of the structure of biomedical and/or biological theories carried out by Darden and Schaffner, I will discuss the problem of the existence of fundamental laws or guide-principles in biology, in the light of the examination of classical genetics accomplished with the instruments of the structuralist conception of theories.